Comparison of Shear Bond Strength of Three Generations of Resin Bonding Agents and Glass Ionomer to Dentin - Mohammad Atefat; Mostafa Sadeghi (Islamic Dental Association of Iran, 2015)
Background and Aim: Due to specific properties of dentin, such as tubular structure and intrinsic moisture, bond to dentin is more difficult than to enamel. The purpose of this study was to compare the shear bond strength (SBS) of composite resin to dentin using three different types of resin bonding agents and a glass ionomer-based adhesive. Materials and Methods: In this in vitro study, 72 premolar teeth without caries or resto-rations were selected and randomly divided into six groups of 12. The first group (I) was chosen as the control group and received no preparation of dentin surface. The remaining groups received application of Single Bond (group II), OptiBond XTR (group III), All-in-One (group IV) and GC Fuji Bond LC adhesive as pre-cure (group V) and co-cure (group VI) on dentin surface, respectively. The samples were stored for two weeks in water at room temperature and then their SBS was measured using Zwick universal testing ma-chine with a crosshead speed of 1mm/min. Statistical data were analyzed using One-way ANOVA and Tamhane's T2 test. Results: The group bonded with OptiBond XTR had the maximum SBS (24.05±9.43 MPa) while the control group showed minimum SBS (0.68±0.32 MPa). SBS of composite resin to dentin in groups V and VI bonded with GC Fuji Bond LC adhesive was signifi-cantly lower than that in groups bonded with resin bonding agents (P<0.05). Conclusion: Based on the results, application of GC Fuji Bond LC glass ionomer adhe-sive is not recommended to bond composite to dentin.